Argentina : First Review Under the Stand-By Arrangement and Exchange System. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The transitional program is broadly on track and quantitative program targets have been met, but structural reforms have been delayed. There are still risks to revenues and expenditures from possible judicial decisions, and the fiscal program may need to be adapted for changes in the macroeconomic framework. Monetary policy continues to face significant uncertainties, and priority needs to be given to providing a predictable regulatory framework for the banking system. Policy preparation can facilitate the transition to the new government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet